2012
DOI: 10.1002/cvde.201106973
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Titanium Dioxide Gas Sensors by the Electric Field Assisted Aerosol CVD Reaction of Titanium Isopropoxide in Toluene

Abstract: Thin films of titanium dioxide are deposited on gas-sensor substrates at 450 8C from the aerosol-assisted (AA)CVD of titanium isopropoxide solutions in toluene under the influence of electric fields. Electric fields are generated by applying a potential difference between the inter-digitated electrodes of the gas-sensor substrate during the deposition. The deposited films are analyzed and characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy (RS). It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
(55 reference statements)
2
28
0
Order By: Relevance
“…In addition, Panjawi et al reported the fabrication of TiO 2 thin films on gas-sensor substrates at 450 C via the AACVD of titanium isopropoxide solutions in toluene [94]. As shown in Fig.…”
Section: Solventmentioning
confidence: 98%
“…In addition, Panjawi et al reported the fabrication of TiO 2 thin films on gas-sensor substrates at 450 C via the AACVD of titanium isopropoxide solutions in toluene [94]. As shown in Fig.…”
Section: Solventmentioning
confidence: 98%
“…Indeed it is well known that sensor microstructure plays an important role in determining the gas response of a gas sensing material [24]. We have suggested previously that a variety of phenomena may be occurring when an electric field is applied to CVD growth [10][11][12][13]. Applied electric fields can cause an increase in growth rate and nucleation rate leading to pseudo dendritic type morphologies as a result of accelerating gas phase species towards the surface [10].…”
Section: Discussionmentioning
confidence: 97%
“…In these cases, we feel this is unlikely to occur as a result of a gas phase effect given that the tungsten hexaphenoxide and titanium tetraisopropoxide precursors are electrically symmetrical. The changes in surface feature scale length hints at a surface effect where growth is directed through a localised electric field rather than as a result of solely gas phase effects [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations